Optimization algorithms for multipath transfer over asymmetric paths using concurrent multipath transfer stream control transmission protocol - Abass, Abdulridha Hanash (2016)
The Internet has evolved in three directions over the past decades. First, content has evolved from relatively low-bandwidth content static text and web pages to highbandwidth content multimedia which results in a significant and growing amount of bandwidth demand. Second, its usage has explosively globalized. Third, Internet access nature has changed from fixed access through desktop computers to a mobile access via smart phones and tablets. As a result, the principles of the Internet design are no longer suitable for current and future applications (e.g., mission-critical and time-critical applications). Network resources management is a key success for the future Internet. Furthermore, in the last decade hosts have equipped with multiple interfaces. Clearly, that led to the desire of applying load sharing to utilize all paths simultaneously to enhance application payload timeliness, and improve resilient to problems on a particular path. Readily apparent, Transport layer is the only layer that realizes a path congestion control and flow control. In addition, a Transport layer that realizes multi-homing does not require modifying the applications or changing the Network layer protocol. The Stream Control Transmission Protocol (SCTP) is an emerging multihoming general purpose Transport layer protocol. An extension of SCTP denoted as Concurrent Multipath Transfer Stream Control Transmission Protocol (CMTSCTP) realizes load sharing functionality. This protocol works well for symmetric paths. But, in reality symmetric paths are unlikely in networks such as Internet. More, multi-homing offers link failure tolerance at Network layer by using different access technologies simultaneously to connect through. Different access technologies clearly imply highly asymmetric paths. CMT-SCTP over asymmetric paths does not work that neatly. In this thesis, phenomena affects CMT-SCTP in asymmetric paths are demonstrated. A comprehensive analysis to understand its nature is presented. Mechanisms that promote CMT-SCTP performance are implemented and evaluated in simulation in order to show their effectiveness. In particular, a combination of multiple mechanisms is vital to make CMT-SCTP works more neatly under a wide range of network and system parameters. Intrinsically, retransmission strategy controls retransmission behavior when a sender fails to receive acknowledgements for sent data due to reorder, lost or corrupted packets. An efficient retransmission strategy would help to vitiate buffer blocking. A new retransmission strategy denoted as Rtx-HYBRIDMETRIC takes into account path’s loss rate and delay is explored. The simulation results show that Rtx-HYBRIDMETRIC retransmission strategy performs well for both failure and non-failure scenarios in a real configuration. In addition, Taxonomy for SCTP retransmission strategies is developed. More, an accurate ROUND TRIP TIME (RTT) is crucial since it is the core of the RTO. The RTO must be correctly set to achieve good performance. Interestingly, CMT-SCTP efficiency is improved by delayed acknowledgement despite additional delay is introduced. However, delayed acknowledgement may lead to inaccurate RTT on asymmetric paths. A new strategy called as Immediate SACK RTT samples (IS-RTT) is developed for accurate RTT on asymmetric paths. The simulation results show that IS-RTT strategy can significantly optimize the RTT estimation on asymmetric paths. Finally, CMT buffer split strategy holds equipoise distribution of buffer space among asymmetric paths. It reveals tradeoff between giving individual path application payload throughput guarantees and maximizing application payload throughput. A new strategy denoted as Quick Response Delayed Acknowledgement for CMT (QR-DAC) is integrated with buffer split strategy. The simulation results show that application payload throughput in a real configuration is optimized over asymmetric paths loss rate.